Maternal mortality : report of meeting held at Friends' House. Euston Road on November 15, 1932 (London : Maternal Mortality Committee)
1932-11 1932 1930s 36 pages have at our disposal under the existing laws. Nor at the present moment would it be right to embark upon any elaborate scheme of investigation into the causes of morbidity, for this reason, because we already know what we have to do, we already know the goal which lies before us, and we would not be justified in exhausting effort, in exhausting resources upon the accumulation of knowledge which could only tend to confirm conclusions which we have already firmly established. Such is the present situation of this social evil, such are the lines of advance which we see before us, such are the means by which it is possible at the present to fulfil them, and draw them to that conclusion which we all desire to see. Let me summarise the matter in three sentences as regards our common object, our common goal. Whatever may be the financial necessity of a nation, we can never neglect to maintain in full efficiency its essential health services. However much we may be impressed with the importance of this service or that, in view of the present facts with which I have dealt, in view of the undiminishing maternal mortality which I have defined to you, we are resolved to set the problem of the maternal mortality rate in the very forefront of our programme of national health services, and, lastly, we remind ourselves that the truest economy is to maintain the health and welfare of the nation in this most essential particular. Ladies and gentlemen, such are the thoughts which I would suggest to you to-day, but there is a thought in my own mind to which I would try to give expression before I resume my seat, a thought ever-present in the minds of all of us who have once had our attention called to this problem. Many things are questioned in these days, many things to which reverence was once paid are questioned and are deprived of that reverence to which some of us think they are still entitled, but never in any heart which retains any of the true feelings of humanity have we yet found any question of the reverence and the regard which is due to motherhood. Look back in time, look far back in time, look so far back that you can see how it was that those feelings, those sentiments which are upon humanity at the present time first arose, and I think if you look back at early man, man who was just beginning to be man and no longer a beast, you will see that the window, the window of the spirit through which the light of mercy and gentleness first shone in and made him human was regard and reverence for the mother and the child. That fact in our history ranking us as something better than mere animals is still a fact, and now, when the spirit of man has so much developed, has made such advance, has advanced to the conquest of mighty empires of mental things, it still remains true that the coming of the full light of reason has only taught us all the more that consideration, regard, attendance for the mother and the child (10) 292/824/1/45